What Trucking Deregulation Did for Florida's Produce and Ornamentals - Richard Beilock (EDIS)
From the late 1970s through the mid-1980s, economic regulation of interstate trucking was phased out in the United States. Prior to that time, trucking firms had to seek federal permission to haul many types of cargoes and there were restrictions on the rates that could be charged (note: in practice, rate restrictions prevented carriers from lowering their charges more often than the reverse). Deregulation of airlines occurred about the same time. Whenever a flight is delayed or a meal is either absent or not up to expectations, everyone loves to blame it on deregulation, rightly or wrongly. The same is true for trucking deregulation. This report will examine an important positive effect of deregulation on motor carriers and the Florida produce and ornamentals industries. This is EDIS document, FE544, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2005.